The use of radar for object detection in vegetated regions - Pătru PÎRJOL, Ph.D (Bulletin of "Carol I" National Defense University, 2023)
The FOPEN radar uses frequencies at VHF and UHF to penetrate the foliage of trees or buildings and detect bodies and people hiding under their cover. FOPEN is an important technology, being located on airborne and ground-based platforms and designed to aid surveillance of very large areas, especially those areas rich in vegetation, which are unsuitable for detection and identification using other sensors. The information the FOPEN radar provides ensures the necessary support for civil or military activities. The civilian use of FOPEN ensures the fulfillment of surveillance and monitoring missions of the Earth’s surface. The data provided will ensure the study of biodiversity, forests, land surface, etc. through the potential of this radar to detect bodies under the canopy of trees.The military use of FOPEN ensures the detection of enemy forces and assets concealed under foliage, whether they are moving or not. The images generated by FOPEN ensure the detection of targets by electromagnetic waves penetrating foliage or buildings, countering adversary camouflage, concealment, or deception techniques. The data provided by FOPEN ensures the necessary information support for decision-making processes during mission planning and execution.